2022
DOI: 10.3390/antib11020035
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Immunity and Antibody Response: Challenges for Developing Efficient COVID-19 Vaccines

Abstract: Questions and concerns regarding the efficacy and immunogenicity of coronavirus disease 2019 (COVID-19) vaccines have plagued scientists since the BNT162b2 mRNA vaccine was introduced in late 2020. As a result, decisions about vaccine boosters based on breakthrough infection rates and the decline of antibody titers have commanded worldwide attention and research. COVID-19 patients have displayed continued severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-spike-protein-specific antibodies and neutral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…Our findings support the hypothesis that long-lasting immunity against SARS-CoV-2 variants will be difficult to achieve through vaccines based solely on the spike protein and using neutralizing antibodies as an efficacy endpoint. One strategy to achieve long-term immunity against COVID-19 is the development of T-cell vaccines ( 9 , 55 ). When designing such vaccines, it is important that the epitopes selected are as invariant as possible and cover the maximum number of HLA haplotypes with even affinity distribution between HLA alleles ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the hypothesis that long-lasting immunity against SARS-CoV-2 variants will be difficult to achieve through vaccines based solely on the spike protein and using neutralizing antibodies as an efficacy endpoint. One strategy to achieve long-term immunity against COVID-19 is the development of T-cell vaccines ( 9 , 55 ). When designing such vaccines, it is important that the epitopes selected are as invariant as possible and cover the maximum number of HLA haplotypes with even affinity distribution between HLA alleles ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although existing studies have shown that neutralizing antibody levels produced by vaccination or COVID-19 infection decrease over time, several investigations on the duration of antibody responses suggest long-term general humoral immunity can be observed up to 8 to 12 months after infection in convalescent patients [ 17 , 18 ]. The number of SARS-CoV-2 antigen-specific memory B cells remains stable for at least 6 to 12 months [ 18 ], and B-cell clonal selection and accumulation accompanied by neutralizing antibody release [ 19 ] support the persistence of humoral immunity after infection [ 20 ]. In terms of vaccine-induced immunity, Moderna studies have demonstrated that clinical trial participants maintained high levels of antibodies within 6 months after receiving the second dose of their mRNA-1273 vaccine [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic first arose in Wuhan, China, and the underlying agent is severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1] . Disease presentation ranges from asymptomatic to multi-organ failure, with an overall fatality rate of 5% (95% CI 1-11) [2] , [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%